Participant experience in a longitudinal online research registry: Associations between ethnocultural identity, educational attainment, and participant feedback in the Brain Health Registry. (20th December 2022) - Ashford, Miriam T.; Eichenbaum, Joseph; Jin, Chengshi; Neuhaus, John; Ulbricht, Aaron; Camacho, Monica R; Fockler, Juliet; Flenniken, Derek; Truran‐Sacrey, Diana; Mackin, R Scott; Maruff, Paul; Weiner, Michael W.; et al.
Abstract: Background: Research registries focused on brain diseases, such as Alzheimer's disease and related dementias (ADRD), have been developed to accelerate clinical study recruitment. Completion of registry components can affect the representativeness of registry populations and data, especially where retention is critical. This study aims to provide insights for online research and retention by studying participants' perceptions of the Brain Health Registry (BHR), with a focus on those from different ethnocultural and socioeconomic backgrounds. Method: BHR is a public online registry for recruitment and longitudinal assessment focused on cognitive aging and ADRD research. Participants can provide feedback to the study team about their overall experience at any time using a questionnaire and are asked to complete feedback questionnaires after completing the Cogstate Brief Battery (CBB) (Table 1). Multivariable ordinal logistic regression estimated associations between sociodemographic characteristics (ethnocultural identity and education attainment) and feedback responses. All analyses covaried for age and gender. Result: Of all participants (N = 89, 673), 5, 469 (6.1%) provided feedback about their overall BHR experience and 14, 676 (16.4%) provided feedback about CBB (Table 2). See Table 3 for associations between sociodemographic characteristics and feedback responses. Identifying as Latino was associated with a poorer experience with the cognitive assessment. Identifying as Latino or non‐White was associated with perceiving the cognitive assessment instructions as less clear and rating that additional help for cognitive assessment instructions would be useful. Higher educational attainment was associated with perceiving BHR site as easier to use and the instructions as clearer, as well as rating additional help for cognitive assessment instructions as less useful. Conclusion: Our findings highlight the need to improve and/or tailor online cognitive assessment design and instructions to better suit the needs of diverse ethnocultural and educational populations. More research is needed to deepen insight into improvements in cognitive assessment design to facilitate engagement and retention of diverse populations.